AN EXPERIMENTAL STUDY INTO THE RHEOLOGY OF SYNTHETIC POLYCRYSTALLINE COESITE AGGREGATES - Renner J.; Stöckhert B.; Zerbian A.; Röller K.; Rummel F. (My University, 2001)
Coesite has been found as a relic in ultrahigh pressure metamorphic (UHPM) crust worldwide and is expected to play a major role in the mechanical behavior of continental crust at UHPM conditions. We performed triaxial compression tests on synthetic polycrystalline coesitite in a solid medium apparatus at confining pressures of 3.1 to 3.7 GPa, temperatures of 700° to ~1160°C, and strain rates between 6×10-7 and 1×10-3s-1. The problem of the limited stress resolution of the solid medium apparatus was addressed by applying two extreme friction corrections that yield lower and upper bounds to the differential stress. The correlation between the mechanical data and the microstructural record of the deformed samples, as a function of temperature and imposed strain rate, is consistent with deformation by dislocation creep. We deduced parameters of a power law (ε=A*sigman*exp[-Q/RT]) as n~3+/-1 and Q~275+/-50kJmol-1. Extrapolation of the experimental data to natural conditions cannot be constrained by comparison with natural microstructures, due to the lack of preserved coesite other than as single crystal inclusions. Nevertheless, the extrapolation indicates a low strength (of order 10 MPa) for natural strain rates at typical UHPM conditions. Absent deformation of the UHPM Brossasco granite (Dora Maira Massif, Western Alps) thus implies low stresses; deformation must have been localized in very weak shear zones during burial and exhumation.